Providing Legal Protection for Consumers Against Standard Clauses/One-sided Agreements Made by Business Actors - Perdana, Surya; Koto, Ismail (DE LEGA LATA: JURNAL ILMU HUKUM, 2024)
Standard clauses are usually made by parties in a stronger position, which in reality can be held by business actors. The contents of standard clauses often harm the party receiving the standard clause, namely the consumer, because they are made unilaterally. If consumers reject the standard clause, they will not get the goods or services they need, because they will find similar standard clauses elsewhere. Article 1 number 1 UUPK states that, "Consumer protection is all efforts that guarantee legal certainty to provide protection to consumers." Apart from that, regulations regarding consumer dispute resolution as a form of legal protection for consumers are reflected in Article 52, the institution given the authority to carry out supervision is the Consumer Dispute Resolution Agency. Business actors are prohibited from including standard clauses whose position or form is difficult to see or cannot be read clearly, or whose expression is difficult to understand. Business actors are obliged to adjust standard clauses that conflict with Law Number 8 of 1999 concerning Consumer Protection. Standard agreements provide many advantages in their use, but from the various advantages that exist there is another side to the use and development of standard agreements which has received a lot of critical attention from legal experts, namely the weakness in accommodating a balanced position for the parties